Entre histoire de la mémoire et mémoire de l’histoire : esquisse de la réponse épistémo-logique des historiens au défi mémoriel en France - Patrick-Michel Noël (Conserveries Mémorielles)
The discipline of history is rarely studied knowingly through the discourse that its practicians enunciate on their knowledge (savoir). However, the « epistemo-logy » of historians is essential to its comprehension for it constitutes the medium through which the discipline has defined, programmed and justified itself. If this epistemology cuts across the history of the discipline, it becomes more manifest when the basis of its knowledge are challenged, just like the last thirty years in France by the memory craze. Fostered by a series of factors, this craze favors memory over history when it comes to apprehend the past. In response to the challenge, the epistemology of historians subdivided itself into two initiatives resulting from the dialectisation of the concepts of history and memory rendered possible by the memory craze. Historians have programmed a new area of research by objectifying memory: history of memory (a). They also developed a new interest for the past of their discipline in order to better identify themselves as a group and to legitimize their scholarly practice (b). Objectifying and instrumentalizing memory, epistemology allows historians to take the necessary distance from it permitting their discipline to maintain its autonomy from memory, autonomy which forms its principal presupposition as a knowledge. Not only does this knowledge is executed in order to produce a knowledge (connaissance) of the past, it is also formulated via an epistemology which is as important as the institutional infrastructure in its disciplinarization. The study of the epistemology of historians nuances their so-called refusal – which is as much praised than denounced by them – to theorize their knowledge.